Too many children left behind : the U.S. achievement gap in comparative perspective - Bradbury, Bruce (Russell Sage Foundation, 2015)
The belief that with hard work and determination, all children have the opportunity to succeed in life is a cherished part of the American Dream. Yet, increased inequality in America has made that dream more difficult for many to obtain. InToo Many Children Left Behind, an international team of social scientists assesses how social mobility varies in the United States compared with Australia, Canada, and the United Kingdom. Bruce Bradbury, Miles Corak, Jane Waldfogel, and Elizabeth Washbrook show that the academic achievement gap between disadvantaged American children and their more advantaged peers is far greater than in other wealthy countries, with serious consequences for their future life outcomes. With education the key to expanding opportunities for those born into low socioeconomic status families, Too Many Children Left Behindhelps us better understand educational disparities and how to reduce them. Analyzing data on 8,000 school children in the United States, the authors demonstrate that disadvantages that begin early in life have long-lasting effects on academic performance. The social inequalities that children experience before they start school contribute to a large gap in test scores between low- and high-SES students later in life. Many children from low-SES backgrounds lack critical resources, including books, high-quality child care, and other goods and services that foster the stimulating environment necessary for cognitive development. The authors find that not only is a child's academic success deeply tied to his or her family background, but that this class-based achievement gap does not narrow as the child proceeds through school. The authors compare test score gaps from the United States with those from three other countries and find smaller achievement gaps and greater social mobility in all three, particularly in Canada. The wider availability of public resources for disadvantaged children in those countries facilitates the early child development that is fundamental for academic success. All three countries provide stronger social services than the United States, including universal health insurance, universal preschool, paid parental leave, and other supports. The authors conclude that the United States could narrow its achievement gap by adopting public policies that expand support for children in the form of tax credits, parenting programs, and pre-K. With economic inequalities limiting the futures of millions of children, Too Many Children Left Behindis a timely study that uses global evidence to show how the United States can do more to level the playing field.--Provided by publisher.